2014
DOI: 10.1016/j.joen.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Root Canal Therapy Reduces Multiple Dimensions of Pain: A National Dental Practice-based Research Network Study

Abstract: Background Initial orthograde root canal therapy (RCT) is used to treat dentoalveolar pathosis. The affect RCT has on pain intensity has been frequently reported, but the affect on other dimensions of pain has not. Also, the lack of large prospective studies involving diverse groups of patients and practitioners that are not involved in data collection suggest that there are multiple opportunities for bias to be introduced when this data is systematically aggregated. Method This prospective observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…The third null hypothesis was also rejected since the temperature for dental cold sensation was different during treatment. Previous studies evaluating dental sensitivity through self-reports and questionnaires 1 , 12 with Analogue Visual Scale are in accordance with our results 3 , 11 . However, the dental cold sensation threshold remained unaltered in the groups treated with placebo (III and IV), which justifies its use in the study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The third null hypothesis was also rejected since the temperature for dental cold sensation was different during treatment. Previous studies evaluating dental sensitivity through self-reports and questionnaires 1 , 12 with Analogue Visual Scale are in accordance with our results 3 , 11 . However, the dental cold sensation threshold remained unaltered in the groups treated with placebo (III and IV), which justifies its use in the study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the questionnaire contained information regarding the kind of pain experienced, and the period and oral region in which it occurred. This questionnaire is widely used in scientific literature for dental research 12 . It is also used for dental and facial pain studies 3 , 11 .…”
Section: Methodsmentioning
confidence: 99%
“…The present report is based on secondary analyses of data originally collected. The original study was designed to prospectively assess outcomes following root canal treatment (RCT), and details of study methods (18) and outcomes (1922) have been previously reported. In brief, 62 dentists (46 general practitioners and 16 endodontic specialists) from 5 regions (Alabama/Mississippi, Florida/Georgia, Minnesota, Oregon/Washington, and Denmark/Sweden) participated by collecting observational data from endodontic patients in their practices.…”
Section: Methodsmentioning
confidence: 99%
“…Ethical review board approval from each region and from the University of Minnesota was obtained prior to initiation of this research. The study methods have been previously reported (Nixdorf et al 2012), as have details regarding the outcome of "severe" postoperative pain following RCT (Law et al 2014), and they conform to Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guidelines.…”
Section: Brief Overview Of the Studymentioning
confidence: 99%